Polysaccharides from fruit and vegetable wastes and their food applications: A review - Ozcan, Basak Ebru; Tetik, Nurten; Aloglu, Hatice Sanlidere (ELSEVIER, 2024)
Fruit and vegetables are a great source of nutrients and have numerous health benefits. The fruit and vegetable industry produces enormous amounts of waste such as peels, seeds, and stems. The amount of this waste production has increased, causing economic and environmental problems. Fruit and vegetable wastes (FVWs) have the potential to be recovered and used to produce high-value goods. Furthermore, FVWs have a large variety and quantity of polysaccharides, which makes them interesting to study for potential industrial use. Currently, the investigations on extracting polysaccharides from FVWs and examining how they affect human health are increasing. The present review focuses on polysaccharides from FVWs such as starch, pectin, cellulose, and inulin, and their various biological activities such as anti-inflammatory, anti-tumor, anti-diabetic, antioxidant, and antimicrobial. Additionally, applications as packaging material, gelling agent, emulsifier, prebiotic, and fat replacer of polysaccharides from FVWs in the food industry have been viewed in detail. As a result, FVWs can be reused as the source of polysaccharides, reducing environmental pollution and enabling sustainable green development. Further investigation of the biological activities of polysaccharides from FVWs on human health is of great importance for using these polysaccharides in food applications.
Keywords: Polysaccharides; Fruit and vegetable wastes; Pectin; Cellulose; Food packaging; BY-PRODUCTS; PECTIC POLYSACCHARIDE; ASSISTED EXTRACTION; FAT REPLACER; PEEL; STARCH; OPTIMIZATION; ANTIOXIDANT; INULIN; ENCAPSULATION; Biochemistry & Molecular Biology; Chemistry; Polymer Science